2014
DOI: 10.1590/s0100-06832014000500011
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization (15NH4NO3) of palisadegrass and residual effect on subsequent no-tillage corn

Abstract: SUMMARYNitrogen is required in large amounts by plants and their dinamics in corn and perennial forages intercropped is little known. This study analyzed the efficiency of nitrogen fertilization ( 15 NH 4 NO 3 ) applied after corn grain harvest to palisadegrass (Brachiaria brizantha cv. Marandu) in intercrops sown at two times, as well as the N residual effect on the subsequent corn crop. The field experiment was performed in Botucatu, São Paulo State, in southeastern Brazil, on a structured Alfisol under no-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…This is an indication that the N applied at the beginning of the corn growing season was used primarily by the corn crop, which extracted quantities of 180 to 200 kg ha -1 of N in the higher rates (Table 3). This result is in agreement with the observations made by other authors; in order to get a palisadegrass response to N after the corn harvest, a new nitrogen fertilization should be carried out (Pariz et al, 2011;Borghi et al, 2014).…”
Section: Palisadegrass After Corn Harvestsupporting
confidence: 92%
“…This is an indication that the N applied at the beginning of the corn growing season was used primarily by the corn crop, which extracted quantities of 180 to 200 kg ha -1 of N in the higher rates (Table 3). This result is in agreement with the observations made by other authors; in order to get a palisadegrass response to N after the corn harvest, a new nitrogen fertilization should be carried out (Pariz et al, 2011;Borghi et al, 2014).…”
Section: Palisadegrass After Corn Harvestsupporting
confidence: 92%
“…Similar results had been obtained in the second year of wheat in Australia (Ladd et al, 1983). In Brazil, it has been shown that less than 7% of the N applied to palisade grass was recovered in maize plants that followed grass desiccation, and there was no residual effect of the fertilizer applied to this grass (Borghi et al, 2014). Dourado Neto et al (2010) reported that only 7% of the N from plant residues were recovered by crops in the first season and about 9% in the subsequent seasons.…”
Section: N Cycling In Cropping Systemssupporting
confidence: 80%
“…The higher amounts of N and K 2 O applied in topdressing in the second season were due to nutritional deficiencies observed in the corn leaves in the first growing season. On 6/9/2011 and 6/1/2012, grasses were fertilized with 60 kg ha -1 N as ammonium sulfate, following the recommendation of Borghi et al (2014) for areas in the first years under NT.…”
Section: Methodsmentioning
confidence: 99%